524 Preventing motor vehicle-related fatalities: a collaborative project to enhance coronial data capture and use. (1st September 2016) - Richmond, Sarah A; Williams, Devon; Pike, Ian; Huyer, Dirk; Lapointe, Lisa; Macarthur, Colin; Howard, Andrew
Abstract : Background: Child fatalities due to motor vehicle collisions (MVCs) are a significant burden in Canada. Data specific to these deaths are often referenced, yet few Canadian jurisdictions systematically collect comprehensive details of all child occupant and pedestrian MV fatalities reducing the effectiveness of informing and setting targets for injury prevention initiatives. Methods: This project had two objectives; 1): To document the details of injuries and specific crash circumstances of all fatally injured child and youth (0–18 years) occupants and pedestrians through review of two provincial coroner case files (2004–2012). 2): To introduce recommendations toward standardised data collection procedures for use by coroners, specific to child and youth occupants and pedestrians involved in fatal MVC to: a) support revision of procedures, processes, and practices to facilitate detailed data capture by coroners; and b) to improve information transfer to inform prevention initiatives. Results: Phase 1: Review of death investigation files (n = 317) did not allow ascertainment of suitable detail about injuries (56.5%, n = 160), restraint status (38.1%, n = 121) and crash type (7.3%, n = 23). Data obtained in the retrospective review revealed 43% (95% CI: 36.3, 50.0) of cases were side impact collisions, and 40.0% (95% CI: 33.0, 48.0) of the fatalities were reported improperly or unrestrained. Phase 2: A standardised form was developed and provided to each provincial coroner service to facilitate consistent and detailed data collection. Prospective data collection reduced missing data to 0%. Conclusions: Review of data obtained from review of child and youth fatalities demonstrated a significant proportion of deaths followed side impact collisions without use of restraint systems; however, detailed information about MVC circumstances and injury details were not present in the investigation files. Stakeholder involvement plays a pivotal role in attaining data that are imperative to the development of effective injury prevention products, policies and practices.